Architecture as a space for utopia, the case of the Instituto de Investigaciones Científicas, La Plata, Argentina (1968-1973) - Parera, Cecilia (Universidad de Lima. Carrera de Arquitectura, 2020)
The Instituto de Investigaciones Científicas of the Universidad Nacional de La Plata inArgentina refers to two utopias according to the horizons to be reached. At the political level, it expresses the boost given to research, as part of the proposals for economic strengthening of the government’s developmental model. At the architectural level, it is one of the earliest manifestations of “system architecture,” evidencing confidence in technology. This article analyzes a work often ignored: an illustrative work of a productive disciplinary period with regard to optimistic ideas about future development and witness of the turning point of interwar modernarchitecture.